O governo de si e dos outros em estratégias de promoção da saúde através de dispositivos de saúde móvel - Abib, Leonardo Trápaga (2019)
The central objective of this thesis is to analyze how the Movement 21 days for a healthier life (M21), as a mobile health device and public policy, develops and acts for the constitution of the healthy individual in the contemporary. To accomplish this task, nine semi-structured interviews were conducted with the subjects who were involved in the construction and execution of the program. In addition to the interviews were produced navigation records based on the monitoring and reading of the contents present on the website and in the M21 application. Finally, the postings related to the program in social networks were mapped and analyzed as a way of understanding and interpreting the uses and appropriations of M21 recommendations and advice by its users. The data produced were analyzed in the light of conceptual tools of Foucaultian theory, such as biopower, pastoral power and governmentality, in dialogue with authors from the fields of physical education, collective health and the humanities. As a result of the investigation, three major axes of analysis were built: i) M21 within the State Health Department of Espírito Santo (SESA): construction, references and tensions; ii) The M21 and its communication strategies, and; iii) Subjects of M21. As a policy produced by SESA, a series of tensions and disputes around the program were identified due to the different conceptions about public intervention in the area of prevention and health promotion, demonstrating how controversial the debate on this subject is. Already in its digital platforms, the M21 made use of contents guided by the notions of behaviorism and medicalization, mobilizing disciplinary, bio-pedagogical and pastoral strategies to act on individuals. As to the uses and appropriations of M21 contents, it was possible to identify a partial acceptance of the same by the subjects. The nature of the posts analyzed also allows us to relativize the direct impact of M21 on the subjects, due to the variety of themes, counselors, motivations and perceptions pointed out by them.